Pertarungan Jurnalisme dan Sastra dalam Menguak Kebenaran - Wahyuni, Dessy (UI Scholars Hub, 2019)
The existence of facts in journalism can be manipulated, while the truth settles in literature. Although both types of writing, namely news texts, which contain facts, and literary texts, which contain fiction, depart from the same reality, the estuary of the truth in it can be different because it is seen from different perspectives and interests. For these various interests, silencing in journalism often occurs. Facts are circumcised, overhauled, and arranged in such a way as to produce new facts. Meanwhile, in literature, facts are packaged using imagination to disguise the truth as if it did not happen. For this reason, using a functional systemic linguistic approach, the authors uncover various linguistic considerations built by Seno Gumira Ajidarma (SGA) in reducing news in Jakarta Jakarta to fulfill certain interests. Then, the writers also dismantled the formation of meaning behind each text in SGA’s “Saksi Mata”, which contained elements of resistance in literature, by using Derrida’s deconstruction. The result of the study shows that the same facts can be stated in a variety of different and subjective ways. In this case, literary work is an effective tool to voice the truth.